Enhanced autogeneous self-healing of MgO blended composites incorporating with silica fume - Noor Azline, M.n.; Nabilah, A.B.; Nor Azizi, S.; Ernaleza, M.; Farah Nora Aznieta, A.A. (Elsevier, 2023)
Many studies have been conducted on the autogeneous self-healing either using pozzolan or MgO approaches. It is well accepted that MgO adversely affects strength development particularly at an early age. Nevertheless, MgO is well accepted mineral admixture that has a promising self-healing ability for cement-based composites. Numerous efforts have been conducted in overcome the shortcoming of the strength of cement composites due to MgO. Various findings and studies have shown that incorporating MgO with pozzolans can be detrimental to the strength of cement composites; this includes any cement-based material that is incorporated with MgO. Thus, it is necessary to evaluate an appropriate blended cements in combination with MgO that possesses a self-healing ability without compromising its strength development. The study evaluated autogenous self-healing of magnesium oxide (MgO) blended mortar containing silica fume. 5 silica fume was applied into 5MgO blended cements and for systematic analysis, effect of each single binder was also evaluated independently. A single crack was fabricated at 7-day and then, the healing ability was evaluated based on flexural strength test, crack sealing and microstructural analysis. Furthermore, ANOVA was employed to evaluate the significance of enhancement method to the MgO blended cement. The finding indicated that silica fume slightly enhanced self-healing of mortar. Similarly, statistical analysis confirmed that the autogenous self-healing of MgO cement is more pronounced with the addition of silica fume.